2020
DOI: 10.2147/ijwh.s260894
|View full text |Cite
|
Sign up to set email alerts
|

<p>Description of Maternal Morbidities Amongst 1000 Women During Pregnancy in Ambanja, Madagascar – Opportunities and Challenges of Using an mHealth System</p>

Abstract: Background: The estimated burden of maternal morbidities in lower-income countries, such as Madagascar, is high. However, there is still a lack of data on maternal morbidities, in part due to an absence of standardized assessment tools. This cross-sectional study aims to report maternal morbidities among 1015 women in the district of Ambanja, Madagascar, and to describe the advantages and limitations of a mHealth system. Methods: Data were collected using the PANDA (pregnancy and newborn diagnosis assessment) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Supporting our work, a three-month randomized controlled trial found smartphone-delivered intervention more effective than clinic-based group intervention [49]. Similarly, other studies have reported promising impacts of mHealth interventions on antenatal care quality, anemia management, nutrition consumption, and health behavior among pregnant mothers [50][51][52]. Evidence also shows the value of mobile health applications in managing preeclampsia among pregnant women within low-resource environments [53][54][55][56][57].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Supporting our work, a three-month randomized controlled trial found smartphone-delivered intervention more effective than clinic-based group intervention [49]. Similarly, other studies have reported promising impacts of mHealth interventions on antenatal care quality, anemia management, nutrition consumption, and health behavior among pregnant mothers [50][51][52]. Evidence also shows the value of mobile health applications in managing preeclampsia among pregnant women within low-resource environments [53][54][55][56][57].…”
Section: Introductionsupporting
confidence: 75%
“…Take the My Iron Friend app as an example: it has shown that monitoring iron levels can be an intuitive and accessible process, even for those without extensive technical knowledge [52]. Likewise, other apps have received accolades from users for their utility, user interfaces, and overall user experiences [50,51,56,[62][63][64][65][66]. So, as we stand at the intersection of technological advancement and healthcare, the lack of mobile health interventions in India (or LMICs in general) appears increasingly unjustified.…”
Section: Introductionmentioning
confidence: 99%